The effects of Turkish propolis on growth and carcass characteristics in broilers under heat stress - Seven, P. Tatli; Seven, I.; Yilmaz, M.; Simsek, U. G. (Elsevier, 2008)
The present study was carried out to investigate the effects of the ethanol extracts of propolis (EEP) and vitamin C on body weight (BW), body weight gain (BWG), feed intake (FI), feed conversion ratio and carcass characteristics of broilers exposed to heat stress (at 34 degrees C). A total of 660 1-day-old broiler chicks (Ross 308) weas used. The chicks were randomly divided into the one positive control, one control and four treatment groups. Sixty broilers were chosen at random for the positive control group, and they were selected as three replicate groups each containing 20 animals in a thermoneutral chamber (average 24 degrees C). Six hundred broilers were randomly selected for the heat stress chamber. Three replicate groups of 40 chicks were assigned to each of the control and four treatment groups. The subjects were exposed to high temperature (34 degrees C) for 41 days. The experimental groups were as follow; group I (positive control) and group II (control) were fed with a basal diet, group III (vitamin C) was fed with basal diet supplemented with 250 mg vitamin C as ascorbic acid/kg, group IV (EEP-0.5) was fed with basal diet supplemented with 0.5 g EEP/kg, group V (EEP-1) was fed with basal diet supplemented with I g EEP/kg, group VI (EEP-3) was fed with basal diet supplemented with 3 g EEP/kg. BW of the control group (41th day) decreased significantly compared to the positive control and supplement groups (except EEP-0.5 group) (P<0.05). The BWG values indicated that the supplements have accelerated the weight gain significantly (P<0.05) between the days 36 and 41. In addition, the positive control and EEP-3 groups were statistically different than the other groups (P<0.05) overdays 3-41. The EEP-3 group was significantly higher than the vitamin C group for BW,
Keywords: Heat stress; Performance; Carcass; Propolis and broiler